Application Notes and Recommendations on using TMS320F28335 Digital Signal Processor to Control Voltage Source Converters - Barbieri, F.; Chandrasena, Ruwan Pathiranage Sarath; Shahnia, Farhad; Rajakaruna, Sumedha; Ghosh, Arindam (Institute of Electrical and Electronics Engineers (IEEE), 2014)
This paper presents general recommendations on utilizing TMS320F28335 Digital Signal Controller (DSC) as the controller for Voltage Source Converters (VSC). First, a comparison is provided on different DSCs that can be used for such applications and the reasons for selecting this specific Texas Instrument device are discussed. Later, the strategy for realtime algorithm developed in the DSC, also referred to as digital Signal Processor (DSP) is explained and its main features that are used for VSC control are described. Some new functions are developed and their characteristics and specifications are summarized. The paper also presents a discussion on the most probable difficulties when programming the DSC/DSP for VSC control applications followed by some improvement methods proposed for tackling these difficulties.